Показатели эффективности функционирования системы радиочастотного мониторинга по контролю излучений РЭС и загрузке полос частот общего пользования - Ковшар, В. А.; Задонский, А. И.; Галкин, С. А.; Сидак, А. С. (ХНУРЭ, 2011)
On the basis of the space-frequency-time approach, a regional evaluation of the performance of subsystems of the radio frequency monitoring. We present elaborate system of quantitative indicators of the efficiency of regional subsystems of the radio frequency monitoring and its tools: fixed, mobile and portable radio stations of technical radio. Identified the procedure for calculating of them.
Keywords: радиочастотный мониторинг; радиочастотный ресурс